2013
DOI: 10.1007/978-94-007-6996-0_14
|View full text |Cite
|
Sign up to set email alerts
|

A Hill Climbing Algorithm for Ground Station Scheduling

Abstract: Ground Station Scheduling arises in satellite mission planning and belongs to scheduling family with time windows. It is know for its high computational complexity and hardness to solve to optimality. In fact, in some cases it is even hard to find a feasible solution that satisfies all user requirements and resource constraints. In this paper we present a Hill Climbing (HC) algorithm for the problem, which is a fast local search algorithm. Despite of being a simple search method, HC showed a good performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Lee et al [8] proposed a heuristic algorithm named "first finished first serviced" to handle COMS scheduling of Korea. Xhafa et al [9] adopted a heuristic hill climbing algorithm based on the characteristics of a satellite data downlink process. Vazquez et al [10,11] employed a heuristic deconflicting operation when conflicts were found: firstly, moving passes to a different antenna at the same site or at another site; secondly, shortening the passes' time slot on the antenna and then formulating a global integer linear programming model that simultaneously contained all these deconflicting operations.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [8] proposed a heuristic algorithm named "first finished first serviced" to handle COMS scheduling of Korea. Xhafa et al [9] adopted a heuristic hill climbing algorithm based on the characteristics of a satellite data downlink process. Vazquez et al [10,11] employed a heuristic deconflicting operation when conflicts were found: firstly, moving passes to a different antenna at the same site or at another site; secondly, shortening the passes' time slot on the antenna and then formulating a global integer linear programming model that simultaneously contained all these deconflicting operations.…”
Section: Introductionmentioning
confidence: 99%